1996
DOI: 10.1093/nar/24.5.924
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Transcription Factor IIIA-DNA Interactions by Xenobiotic Metal Ions

Abstract: Transcription factor IIIA (TFIIIA), a cysteine-rich regulatory protein, is the prototype for the largest known superfamily of eukaryotic transcription factors. Members of the TFIIIA superfamily contain Cys2His2 zinc finger domains responsible for nucleic acid binding. Xenobiotic metal ions, which lack known biological function, were previously used as probes for the structure and function of steroid hormone receptors which contain Cys2Cys2 zinc finger domains. Structural alterations in cysteine-rich regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 33 publications
5
50
0
2
Order By: Relevance
“…Besides inducing ROS, Al inhibits DNA repair enzymes that contain zinc finger domains [Hanas and Gunn, 1996]. Cui et al [2003] recently demonstrated that Al impairs the ligase step of DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…Besides inducing ROS, Al inhibits DNA repair enzymes that contain zinc finger domains [Hanas and Gunn, 1996]. Cui et al [2003] recently demonstrated that Al impairs the ligase step of DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports indicate that foreign metal ions can replace Zn 2+ in various zinc finger proteins and, in so doing, impair or alter their functions [20][21][22][23][24][25][26][27]. For example, exposure to Cd 2+ inhibits the binding of transcription factors such as TFIIIA and MTF-1 to their cognate DNA sites [19,27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, exposure to Cd 2+ inhibits the binding of transcription factors such as TFIIIA and MTF-1 to their cognate DNA sites [19,27]. In contrast, another Cd-substituted zinc finger protein, Sp1, retains its capacity to bind specifically to DNA [28].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the reaction of apoMT and one of its component peptide sequences with Cd-carbonic anhydrase showed that both were remarkably effective in competing for protein-bound Cd 2+ [31,32]. There is evidence that, in vitro, Cd 2+ can substitute for Zn 2+ in zinc-finger structures and that such substitution can change the activities of the finger domains [22,28,33]. Therefore, this study has also examined how Cd-TFIIIA reacts with apo-or Zn 7 -MT.…”
Section: Introductionmentioning
confidence: 99%